2003
DOI: 10.1017/s0012162203001282
|View full text |Cite
|
Sign up to set email alerts
|

Attention-deficit– hyperactivity disorder with and without oppositional defiant disorder in 3- to 7-year-old children

Abstract: Attention-deficit-hyperactivity disorder (ADHD) is a common neurodevelopmental disorder with a high degree of associated behavioural problems. In order to study characteristics of ADHD with and without oppositional defiant disorder (ODD) in a representative group of young children with clinical impairment in Sweden, 131 children (101 males, 30 females) with ADHD (mean age 5 years, SD 1 year 5 months; range 3 to 7 years) were clinically examined, and their parents interviewed. Independent questionnaire data (Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 29 publications
2
29
0
Order By: Relevance
“…We found that children with symptoms of ADHD and co-occurring ODD were more impaired than children with ADHD alone, which is also in line with the findings of previous preschool studies (5,17,20), although neither group significantly differed from the group of children with co-occurring CD. To our knowledge, no previous preschool studies have compared the impact of the comorbidity of ODD versus CD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that children with symptoms of ADHD and co-occurring ODD were more impaired than children with ADHD alone, which is also in line with the findings of previous preschool studies (5,17,20), although neither group significantly differed from the group of children with co-occurring CD. To our knowledge, no previous preschool studies have compared the impact of the comorbidity of ODD versus CD.…”
Section: Discussionsupporting
confidence: 92%
“…Comorbid behavioral disorders -namely oppositional defiant disorder (ODD) and conduct disorder (CD) -have been found to be strongly associated with elevated levels of impairment in both school-aged children with ADHD (8;12-16) and preschoolers with ADHD (4,5,17,18). In most preschool samples, ODD and CD have been merged into one disruptive disorder construct when examining the impact of the comorbidity of ADHD (18)(19)(20). However, longitudinal studies have suggested that children with ADHD and cooccurring ODD may have a different developmental course than those with co-occurring CD (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies of CD/ODD in preschool children in the general population are rare (Kadesjö, Hagglof, Kadesjo, & Gillberg, 2003;Kim-Cohen et al, 2005;Egger & Angold, 2006). Furthermore important nosological questions remain, for example the contribution of callous-unemotional symptoms, the importance of gender differences, and the relationship between ODD, CD and anti-social personality disorder (Moffitt et al, 2008).…”
Section: Risk Factors and Correlatesmentioning
confidence: 99%
“…Studies have shown that as many as 65% of youth with ADHD have ODD (Biederman et al, 1996b;Kadesjo and Gillberg, 2001;Kadesjo et al, 2003). The behaviors characterizing ODD --temper outbursts, persistent stubbornness, resistance to directions, unwillingness to compromise with adults or peers, deliberate or persistent testing of limits, and verbal (and minor physical) aggression --compound the difficulties of children with ADHD (Biederman et al, 1987;Biederman et al, 1991).…”
Section: Introductionmentioning
confidence: 99%